Materials per a l'anàlisi multilingüe i contrastiva de locucions, col·locacions i fraseologia. Un escandall quant a Ausiàs March i «Tirant lo Blanch» - Martines, Vicent (Caplletra. Revista Internacional de Filologia, 2006)
This essay offers a sampling of a multilingual contrastive analysis of poems by Ausiàs March and the ones in «Tirant lo Blanch» (original versions and their respective translations) as regards locutions, collocations and phraseology. These elements are fully characteristic of the literary language of any author and, at the same time, they indicate his degree of command of his vehicular language or of the language for literary creation. In addition, they turn out to be important –and often problematic– questions as far as their translation is concerned, precisely because the text has to be‘naturalised’ in the receiving language and its cultural tradition. And this is so because, while translating, the words and their nets of syntantic and semantic interdependencehave to be taken into account. As a consequence, the necessary elements to be able to calibrate in detail the clauses of morphosyntactic and semantic commitment atsyntagmatic reach will be available. Therefore, it will be feasible to carry out case analysis regarding ‘environments’ or essential attributes for the characterization –and the understanding– of the literary language of our reference authors.